Factors that have helped the existence and prosperity of trade relations between Egypt and the country of India - Khalifa, Naima Abu Al-Qasim Al-Suwaiyee; Mogani, Wan Kamal (Arab Journal for Sciences and Research Publishing, 2019)
This research, which is named by (the factors that assisted the existence and prosperity of trade relations between Egypt and the country of India) is the most important points that formed the Link tool to, also it said The geographical location of both countries, the impact of the spread of Islam on the movement of the economy between the two countries, and then deal with the most important geographical features that helped to support the trade movement, which was in the Red Sea and the coasts and ports established in that period, in addition to marine currents and monsoon, and the important relations held by the Muslim princes to suit their commercial interests